2012
DOI: 10.3892/ijo.2012.1400
|View full text |Cite
|
Sign up to set email alerts
|

PKD1 negatively regulates cell invasion, migration and proliferation ability of human osteosarcoma

Abstract: Abstract. Osteosarcoma (OS) is a primary malignancy of the bone, with a tendency to metastasize early. Despite intensive chemotherapy and surgical resection, more than 30% of patients develop distant metastases, and the prognosis of patients with metastases is essentially poor. Members of the protein kinase D (PKD) family are serine/threonine kinases, and have been studied in various cancers. Among the three different isoforms of this family, PKD1 is one of the best understood for its role in human malignancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The expression patterns and effects of PKD isoforms differ among various types of cancer. PKD1 is reported to play an inhibitory role in cell migration and invasion of several malignancy [ 27 - 30 ]. PKD2 and PKD3 are overexpressed in some highly invasive cancer cells and are demonstrated to accelerate cancer cell invasion through the AKT, ERK and NF-κB signaling pathways [ 4 , 14 , 26 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression patterns and effects of PKD isoforms differ among various types of cancer. PKD1 is reported to play an inhibitory role in cell migration and invasion of several malignancy [ 27 - 30 ]. PKD2 and PKD3 are overexpressed in some highly invasive cancer cells and are demonstrated to accelerate cancer cell invasion through the AKT, ERK and NF-κB signaling pathways [ 4 , 14 , 26 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, loss of PKD1 has been associated with increased invasiveness and risk of metastases in gastric cancer and osteosarcoma [39,40]. We previously have shown the importance of PKD1 for breast cancer cell invasion by demonstrating that a knockdown of PKD1 in the low invasive breast cancer cell line MCF-7 led to an increase of its invasive potential, and reexpression of a constitutively active PKD1 in highly invasive MDA-MB-231 cells impaired their invasive phenotype [12].…”
Section: Discussionmentioning
confidence: 99%
“…The relative contributions of different endogenous PKD isoforms to both signaling pathways have not been fully elucidated. Puzzling in the PKD literature is that different isoforms, or even the same isoform, have been attributed pro- or anti-migratory functions [12], [14], [17], [18], [19], [20], [21], [22], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44]. For example, for PKD3 it was shown that chemical inhibition [22], but also overexpression of active PKD3 blocked directed cell migration [19].…”
Section: Discussionmentioning
confidence: 99%